The Role of the Sampang Regency Government in Developing Islamic Financial Institutions in Sampang - Arief Tegar Saputra; Siti Nur Rosidah; Afiyanti Wulandari (Penerbit Hellow Pustaka, 2025)
The government has the authority to regulate and create regulations that can advance and increase the development of sharia financial institutions, especially in Sampang district, which in future, with the distribution of sharia financial institutions in each region will also have an impact on significant economic acceleration. The aim of this research is to determine the role of the Sampang district government in developing sharia financial institutions in Sampang. The method used in this research is qualitative research using the literature review or library review research method. Using data processing techniques, analyzing articles, books, or scientific papers in previous research is then concluded and summarized into an article.